2020
DOI: 10.1093/mnras/staa1490
|View full text |Cite
|
Sign up to set email alerts
|

Lyman α absorption beyond the disc of simulated spiral galaxies

Abstract: We present an analysis of the origin and properties of the circumgalactic medium (CGM) in a suite of 11 cosmological zoom simulations resembling present-day spiral galaxies. On average the galaxies retain about 50 per cent of the cosmic fraction in baryons, almost equally divided into disc (interstellar medium) gas, cool CGM gas and warm-hot CGM gas. At radii smaller than 50 kpc the CGM is dominated by recycled warm-hot gas injected from the central galaxy, while at larger radii it is dominated by cool gas acc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 70 publications
1
16
0
1
Order By: Relevance
“…Our results are also consistent with the N(H i)-b relationship for dwarf galaxies from the NIHAO simulation suite Gutcke et al (2017). The distribution of strong H i absorbers (with N(H i) 10 15 cm −2 ) appears to be less extended compared to more massive, star-forming galaxies in previous numerical works (e.g., Gutcke et al 2017;Röttgers et al 2020). In addition, several recent studies have found that the spacial distribution and covering fractions of the strong H i absorbing systems can be sensitive to instability processes occurring at smaller scales, and thus sensitive to the CGM-resolution cosmological simulations (e.g., Hummels et al 2019;Suresh et al 2019;van de Voort et al 2019).…”
Section: The Circumgalactic Mediumsupporting
confidence: 89%
“…Our results are also consistent with the N(H i)-b relationship for dwarf galaxies from the NIHAO simulation suite Gutcke et al (2017). The distribution of strong H i absorbers (with N(H i) 10 15 cm −2 ) appears to be less extended compared to more massive, star-forming galaxies in previous numerical works (e.g., Gutcke et al 2017;Röttgers et al 2020). In addition, several recent studies have found that the spacial distribution and covering fractions of the strong H i absorbing systems can be sensitive to instability processes occurring at smaller scales, and thus sensitive to the CGM-resolution cosmological simulations (e.g., Hummels et al 2019;Suresh et al 2019;van de Voort et al 2019).…”
Section: The Circumgalactic Mediumsupporting
confidence: 89%
“…Mock absorption spectra are generated through the simulation volume using the spectrum generation tools in the Pygad 2 analysis package (Röttgers et al 2020). The spectra are computed from gas particles who smoothing lengths intersect with the LOS, so spectrum generation is not dependent on our halo-finding procedure.…”
Section: Spectral Generationmentioning
confidence: 99%
“…The resulting ion column densities for each pixel are converted into an optical depth using the oscillator strength of each species. See Röttgers et al (2020) for further details on Pygad.…”
Section: Spectral Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Software: Astropy (https://www.astropy.org/; Astropy Collaboration et al 2018), gizmo (http://www.tapir. caltech.edu/ ∼ phopkins/Site/GIZMO.html; Hopkins 2015; Springel 2005), Matplotlib (https://matplotlib.org/), Plotly (https://plotly.com/), pygad (https://bitbucket.org/broett/pygad/src/master/; Röttgers et al 2020)…”
mentioning
confidence: 99%